PARTISIPASI ORANG TUA MEMASUKAN ANAK DALAM LEMBAGA PENDIDIKAN ANAK USIA DINI DI KECAMATAN SIMPANG HULU KABUPATEN KETAPANG - Plorensia Cindy Tiansi; Aunurrahman Aunurrahman; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the participation of parents in entering children in early childhood education institutions, understanding, supporting factors and inhibiting parents' participation in entering children in early childhood education institutions in Simpang Hulu District, Ketapang Regency. The method used is descriptive qualitative. Data collection techniques using interview techniques and documentation tools, data collection tools, namely a combination of interviews and documentation, technical data analysis, namely data reduction, data presentation, conclusion drawing and verification, and triangulation testing the validity of the data. The results showed that the understanding of parents who included children in early childhood education institutions already understood what early childhood education was based on the results of research and interviews conducted by parents who were able to explain what early childhood education was, but from some parents who included children In early childhood education institutions there are still some parents who do not understand what early childhood education is. The supporting and inhibiting factors for parental participation in early childhood education institutions are economic factors, parents' income, parents' occupations, education costs, parents' understanding of early childhood education and the distance to educational institutions.Keywords: Parental Participation, Early Childhood Education